P303 A CASE OF MYOPERICARDITIS AFTER II DOSE COVID 19 MRNA VACCINE IN YOUNG MALE. (18th May 2022) - Bolognesi, M; Iconomu, E; Armentano, C; Turchio, P; Petrini, M; Moderato, L; Michieletti, E; Aschieri, D
Abstract: COVID 19 disease caused devasting health consequences from March 2020. The development of effective vaccines against SARs COV 2 is an important weapon to defeat this virus. However rare cases of vaccines complications have been reported including myopericarditis above all in young males that we have to follow strictly and to begin right therapy as soon as possible. Data regarding specific therapy about mypericarditis after COVid 19 vaccine are scanty. We report a case of 16 years old male with no health problems, admitted in emergency department with chest pain relieved by sitting posistion and persistent fever rised 24 h after receiving his second dose of mRNA COVID 19 vaccineA 12 lead ECG showed normal sinusal rhythm without ST changes. On admission the complete blood cells count was normal, PCR was high: 5, 92 mg/dl and troponin I at high sensivity was elevated: 9249 ml/L. The patient was hospitalized in our cardiology department with suspected myopericarditis. Ecocardiography TT showed normal left ventricular ejection fraction and no pericardial effusion. We began immediately non steroidal anti inflammatory therapy at high dose (ibuprofen 600 mg x 3/die and colchicine 1 mg/die) with conseguently reduction of chest painfuls symptoms. We also began ACEi therapy. On the advice of of the infectious disease specialist we added in the 5 th day methilprednisolone 25 mg/die in consideration of an excessive acute inflammatory response and we observed a clinical improvement with an indices of inflammation reduction. Cardiac magnetic resonance (CMR) performed after 3 day in T2 weighted images showed intramyocardial and subepicardial hyperintensity localized to the mid and apical lateral, basal infero lateral, distal anterior segment, as myocardial edema. Furthermore after Injection of contrast: subepicardial late gadolinium enhancement in the same segment. Minimum (4 mm) pericardial effusion. The clinical setting was attributable as symptoms, elevated troponin above upper limit of normal, in absence of other identifiable cause of symptoms and findings, to confirmed case of acute myocarditis after vaccine in according to the "CDC case definitions". Myocarditis after mRNA COVID 19 vaccination affect above all young males with mild and multifocal forms with risks and benefits in favour of vaccines. However we need to identify them for an early therapy. In these setting of myocarditis an early use of corticosteroids can be provided.